PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, FINANCIAL LEVERAGE, PERSENTASE PENAWARAN SAHAM, UMUR PERUSAHAAN, REPUTASI PENJAMIN, REPUTASI AUDITOR TERHADAP INITIAL RETURN - Imang Dapit Pamungkas (LPPM Universitas Pekalongan, 2013)
The capital market is a source of business financing and investment alternatives in the securities sector. There are some anomalies that occur when the stock traded in the secondary market. When stock prices in the secondary market is higher than the stock price on the primary market, and there was a positive initial return (underpricing), the inverse is negative initial return (overpricing). The purpose of this study was to determine the influence is there any financial information and non- financial to the initial return on the IPO companies listed in Indonesia Stock Exchange. The population in this study is a company doing an IPO and listed on the Stock Exchange. Samples were taken using purposive sampling method on the company's IPO in 2008-2010. Method of data collection methods documentation. This study uses descriptive analysis and multiple regression analysis.The results showed that the financial information for the company size, profitability influential and non-financial information significant effect on initial returns. Suggestions that can further research is recommended to (1) further research better add factors outside the company in research, (2) adding further researcher financial information and non-financial information. Keywords: Company Size, Profitability, Financial Leverage, Corporate Age, Auditor Reputation, Reputation Underwriters and Initial Return